Koe: Web‐based software to classify acoustic units and analyse sequence structure in animal vocalizations. Issue 3 (9th January 2020) - Fukuzawa, Yukio; Webb, Wesley H.; Pawley, Matthew D.M.; Roper, Michelle M.; Marsland, Stephen; Brunton, Dianne H.; Gilman, Andrew
Abstract: Classifying acoustic units is often a key step in studying repertoires and sequence structure in animal communication. Manual classification by eye and ear remains the primary method, but new tools and techniques are urgently needed to expedite the process for large, diverse datasets. Here we introduce Koe, an application for classifying and analysing animal vocalizations. Koe offers bulk‐labelling of units via interactive ordination plots and unit tables, as well as visualization and playback, segmentation, measurement, data filtering/exporting and new tools for analysing repertoire and sequence structure – in an integrated environment. We demonstrate Koe with a real‐world case study of New Zealand bellbird Anthornis melanura songs from an archipelago metapopulation. Having classified 21, 500 units in Koe, we compare repertoires and sequence structure between sites and sexes. Koe is web‐based (koe.io.ac.nz. ) and easy to use, making it ideal for collaboration, education and citizen science. By enabling large‐scale, high‐resolution classification and analysis of animal vocalizations, Koe expands the possibilities for bioacoustics research.